Preparation method of phosphorus-silicon synergistic flame-retardant nylon

By using phosphorus-silicon co-effect flame retardant and nano-SiO2 in composite nylon materials, the problem of poor safety of existing composite nylon materials is solved, and efficient flame retardant effect and environmentally friendly performance are achieved.

CN116004000BActive Publication Date: 2025-03-14GUANGDONG TAISU NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211696809.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-03-14
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

The existing composite nylon materials are poorly safe, especially during combustion, which may generate toxic and corrosive gases, which damage the equipment and endanger personal safety.

Method used

The new phosphorus-silicon co-acting flame retardant was prepared by synthesizing the intermediate PEPA by pentaerythritol and phosphorus trichloride, and reacting with phenylphosphoryl dichloride. Combining nano SiO2 as a co-acting flame retardant, blending, extruding and granulating to improve the flame retardant performance of nylon 66.

Benefits of technology

It significantly improves the limit oxygen index (LOI) and UL-94 vertical combustion performance of PA66 to reach V-0 level, avoiding the defect of halogen flame retardants producing thick smoke and toxic gases during combustion, and improving the safety and environmental protection of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure DEST_PATH_IMAGE003
    Figure DEST_PATH_IMAGE003
  • Figure 962468DEST_PATH_IMAGE002
    Figure 962468DEST_PATH_IMAGE002
Patent Text Reader

Abstract

The invention discloses a preparation method of phosphorus-silicon synergistic flame-retardant nylon and a preparation method thereof, which belongs to the technical field of flame-retardant nylon composite materials. The invention firstly uses pentaerythritol and phosphorus oxychloride as reaction raw materials to synthesize an intermediate PEPA with a bicyclic cage structure; then, PEPA is further reacted with phenylphosphoryl dichloride to prepare a novel phosphorus-based flame retardant BPEPA with a highly symmetrical structure; then, the flame retardant BPEPA is reacted with nano-SiO 2 The combustion performance of PA66 was improved by compounding. When the addition amount of BPEPA was 20wt%, nano-SiO 2 When the addition amount is 4wt%, the LOI of the product is increased from 24% of pure PA66 to 28.6%, and the UL‑94 vertical combustion performance of the product reaches the V‑0 level; while achieving a good flame retardant effect, the environmental and personal safety problems caused by halogen-containing flame retardants are avoided. Therefore, the present invention solves the technical problem of poor safety of composite nylon materials in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame-retardant nylon composite materials, and in particular to a preparation method of phosphorus-silicon synergistic flame-retardant nylon. Background Art

[0002] Compared with traditional metal materials or inorganic non-metallic materials, plastics not only have excellent physical and chemical properties, but also have simpler preparation processes. Therefore, plastics are widely used in various fields today. Nylon, also known as polyphthalamide, is abbreviated as PA in English. It is a high molecular polymer characterized by phthalamide groups, i.e. -CO-NH carbon chains. Nylon is a typical thermoplastic resin. At the same time, it has many types, large output, and excellent performance. Therefore, nylon occupies the largest proportion of general engineering plastics. Among the many types of nylon, nylon 66, i.e. PA66, has the largest output and consumption, and its products are mainly used in aviation, automobiles, machinery, electronics, chemicals, construction and other fields.

[0003] The UL-94 vertical combustion performance of PA66 is V-2 level, and the limiting oxygen index LOI is 24%, that is, the material of PA66 itself has certain flame retardant properties. At present, the flame retardants used in PA66 in industry are mainly halogen and phosphorus nitrogen. Halogen flame retardants are cheap, and a small amount of addition can achieve an ideal flame retardant effect. At the same time, the mechanical properties of the nylon matrix are less damaged, so they are widely used in flame retardant additives for nylon materials. Based on this, Chinese patent CN102382297A discloses a rare earth flame retardant composite nylon material, which adds caprolactam, MoS2, La2O3, decabromodiphenylethane, TDI, and carbon black according to a certain weight ratio, adds them into a reactor for heating, stirring and vacuuming at the same time to form a molten material, and after keeping it in a boiling state for a certain period of time, pours it into a preheated mold, puts the mold into a high-temperature oven, and polymerizes the molten material; after cooling, it is a product. This rare earth flame-retardant composite nylon material has higher wear resistance, combustion-supporting properties, high temperature resistance and corrosion resistance; it can work continuously for 10 hours without change at a temperature of 180 to 220°C; if it burns, it will self-extinguish within 3 seconds of leaving the fire; therefore, it can achieve a flame-retardant effect.

[0004] However, the rare earth flame retardant composite nylon material disclosed above still has the technical problem of poor safety. Specifically, the three elements of combustion are heat, oxygen and combustibles. By preventing or interfering with any one of the elements, combustion can be terminated to achieve the purpose of flame retardancy. It specifically includes increasing the thermal decomposition temperature of the polymer, capturing active free radicals, forming a flame-retardant heat-insulating protective carbon layer, diluting the concentration of combustible gases, absorbing heat, etc. The flame retardant mechanism of the polymer mainly includes the following four aspects: gas phase flame retardant mechanism, condensed phase flame retardant mechanism, interrupted heat exchange flame retardant mechanism and synergistic flame retardant mechanism. The flame retardant nylon disclosed in the prior art, whose effective flame retardant is decabromodiphenylethane, as a halogen flame retardant, it usually plays a gas phase flame retardant mechanism, that is, it can inhibit the combustion gas phase chain reaction, and its decomposition products are mostly inert substances, which can dilute the concentration of combustible gases and also have a covering effect. Except for decabromodiphenylethane, most of the halogen flame retardants commonly used in industry are brominated flame retardants, such as polybrominated diphenyl ethers, brominated phenols or tetrabromobisphenols. The advantages of halogen flame retardants are small dosage, high flame retardant efficiency, wide application range and good thermal stability. However, its disadvantage is that a large amount of thick smoke and toxic and corrosive gases are generated during the combustion process, which damages instruments and equipment, endangers personal safety and pollutes the environment. With the issuance of the WEEE Directive and the RoHS Directive, the use of halogen flame retardants has been basically banned. Therefore, it will be an inevitable trend to develop new flame retardants with the characteristics of halogen-free, safe and environmentally friendly, and high flame retardant efficiency. Summary of the invention

[0005] Based on this, it is necessary to provide a method for preparing phosphorus-silicon synergistic flame-retardant nylon to address the technical problem of poor safety of composite nylon materials in the prior art.

[0006] A method for preparing phosphorus-silicon synergistic flame-retardant nylon comprises the following steps:

[0007] S1: Under nitrogen protection and mechanical stirring, add 80 parts by volume of 1,4-dioxane into a 250-volume four-necked vessel;

[0008] S2: Add 27.2 parts of pentaerythritol and heat to 85°C; after the pentaerythritol is partially dissolved, add 33.66 parts of phosphorus oxychloride into 100 parts by volume of a constant pressure dropping funnel, and slowly and uniformly drip it into the four-mouth container, and the dripping is completed in about 2 hours; keep warm for 20 minutes, then heat to 95°C, and continue the reaction until no obvious hydrogen chloride is discharged from the tail gas;

[0009] S3: Then, in a vacuum drying oven, the mixture is treated at a drying temperature of 90° C. until the weight of the product does not change, to obtain the intermediate product PEPA;

[0010] S4: Next, under nitrogen protection, 100 parts by volume of acetonitrile was added to another four-necked vessel containing 250 parts by volume; then, 39.6 parts of PEPA recrystallized from ethanol was added, and the temperature was raised to 75° C.;

[0011] S5: After PEPA is completely dissolved under magnetic stirring, add 23.23 parts of triethylamine as an acid binding agent.

[0012] S6: After the system is stable for 10 minutes, add 19.5 parts of phenylphosphoryl dichloride into a 100 volume parts constant pressure dropping funnel, and then slowly and uniformly add it dropwise for about 1 hour. After keeping the temperature for 20 minutes, raise the temperature to 90°C and reflux for 8 hours;

[0013] S7: After the reaction is completed, the product is filtered, and then the product is washed with acetonitrile and deionized water respectively; and then the product is dried in a vacuum drying oven at a drying temperature of 90° C. until the weight does not change; thereby BPEPA is synthesized;

[0014] S8: Pre-dry PA66 at 100°C for 10h; then, blend and extrude PA66, BPEPA and nano-SiO2 together; then, granulate them; wherein, the process parameters of each zone of the extruder are: 190°C, 210°C, 260°C, 280°C, 290°C, 290°C, 290°C, 280°C; the temperature of the die head is 280°C.

[0015] Specifically, 1,4-dioxane and acetonitrile were treated to remove water using activated 4A molecular sieves before use.

[0016] Specifically, the molar ratio of phosphorus oxychloride to pentaerythritol is 1.1:1.0.

[0017] Specifically, in step S5, one of pyridine or anhydrous potassium carbonate replaces triethylamine as the acid binding agent.

[0018] Specifically, the molar ratio of PEPA to phenylphosphoryl dichloride is 2.2:1.

[0019] Specifically, the addition amount of BPEPA is 5wt%, 10wt%, 15wt% or 20wt%.

[0020] Specifically, the added amount of nano-SiO2 is 1wt%, 2wt%, 3wt% or 4wt%.

[0021] Specifically, when the addition amount of BPEPA is 20wt%, the addition amount of nano-SiO2 is 4wt%.

[0022] In summary, the preparation method of phosphorus silicon synergistic flame retardant nylon of the present invention first uses pentaerythritol and phosphorus oxychloride as reaction raw materials to synthesize an intermediate PEPA with a bicyclic cage structure; then, PEPA is further reacted with phenylphosphoryl dichloride to prepare a new type of phosphorus flame retardant BPEPA with a highly symmetrical structure; at the same time, the phosphorus content of BPEPA is determined to be 19.03% by the quinoline molybdenum acetone method, which is close to the theoretical value. Then, the optimal synthesis process conditions of the flame retardant BPEPA are determined by the single factor experimental method: acetonitrile is used as the solvent, triethylamine is used as the acid binding agent, the optimal raw material molar ratio PEPA:BPOD=2.2:1, the optimal reaction time is 8h, and the optimal reaction temperature is 90°C. At this time, the yield of BPEPA can reach 60.4%. The flame retardant performance test shows that the flame retardant BPEPA and nano-SiO2 can improve the combustion performance of PA66. When the BPEPA addition amount is 20wt% and the nano-SiO2 addition amount is 4wt%, the LOI of the product is increased from 24% of pure PA66 to 28.6%, and the UL-94 vertical combustion performance of the product reaches the V-0 level. The flame retardant mechanism of phosphorus silicon type flame retardant is that during the combustion process, the phosphorus-containing flame retardant is thermally decomposed into phosphorus-containing depolymers at high temperatures. Such substances can catalyze the formation of the carbon layer of the material, and the decomposition products of the silicon-containing flame retardant during combustion can migrate to the surface of the carbon layer, making the formed carbon layer more stable. The synergistic effect generated by the phosphorus silicon synergy can obtain an ideal flame retardant effect; and it avoids the defects of the halogen-containing flame retardant in the prior art that a large amount of thick smoke and toxic and corrosive gases are generated during the combustion process, which damages instruments and equipment, and endangers personal safety and pollutes the environment. Therefore, the preparation method of a phosphorus silicon synergistic flame retardant nylon of the present invention solves the technical problem of poor safety of composite nylon materials in the prior art. DETAILED DESCRIPTION

[0023] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation mode of the present invention is described in detail below in conjunction with embodiments. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0024] Specifically, the present invention provides a method for preparing phosphorus-silicon synergistic flame-retardant nylon, which comprises the following steps:

[0025] S1: Under nitrogen protection and mechanical stirring, add 80 parts by volume of 1,4-dioxane into a 250-volume four-necked vessel;

[0026] S2: Add 27.2 parts of pentaerythritol and heat to 85°C; after the pentaerythritol is partially dissolved, add 33.66 parts of phosphorus oxychloride into 100 parts by volume of a constant pressure dropping funnel, and slowly and uniformly drip it into the four-mouth container, and the dripping is completed in about 2 hours; keep warm for 20 minutes, then heat to 95°C, and continue the reaction until no obvious hydrogen chloride is discharged from the tail gas;

[0027] S3: Then, in a vacuum drying oven, the mixture is treated at a drying temperature of 90° C. until the weight of the product does not change, to obtain the intermediate product PEPA;

[0028] S4: Next, under nitrogen protection, 100 parts by volume of acetonitrile was added to another four-necked vessel containing 250 parts by volume; then, 39.6 parts of PEPA recrystallized from ethanol was added, and the temperature was raised to 75° C.;

[0029] S5: After PEPA is completely dissolved under magnetic stirring, add 23.23 parts of triethylamine as an acid binding agent.

[0030] S6: After the system is stable for 10 minutes, add 19.5 parts of phenylphosphoryl dichloride into a 100 volume parts constant pressure dropping funnel, and then slowly and uniformly add it dropwise for about 1 hour. After keeping the temperature for 20 minutes, raise the temperature to 90°C and reflux for 8 hours;

[0031] S7: After the reaction is completed, the product is filtered, and then the product is washed with acetonitrile and deionized water respectively; and then the product is dried in a vacuum drying oven at a drying temperature of 90° C. until the weight does not change; thereby BPEPA is synthesized;

[0032] S8: Pre-dry PA66 at 100°C for 10h; then, blend and extrude PA66, BPEPA and nano-SiO2 together; then, granulate them; wherein, the process parameters of each zone of the extruder are: 190°C, 210°C, 260°C, 280°C, 290°C, 290°C, 290°C, 280°C; the temperature of the die head is 280°C.

[0033] Specifically, in the preparation method of phosphorus-silicon synergistic flame-retardant nylon of the present invention, a preparation example of an organophosphorus flame retardant is as follows:

[0034] First, synthesize the intermediate product PEPA, the full name of PEPA is: 1-oxyphospha-4-hydroxymethyl-2,6,7-trioxabicyclooctane; the specific synthesis steps are: under the conditions of nitrogen protection and mechanical stirring, add 80ml of 1,4-dioxane to a 250ml four-necked flask, dehydrate it with an activated 4A molecular sieve before use, and then use it as a reaction solvent. Then, add 27.2g, i.e. 0.2mol of pentaerythritol, and then heat it to 85℃; after the pentaerythritol is partially dissolved, add 33.66g, i.e. 0.22mol of phosphorus oxychloride to a 100ml constant pressure dropping funnel, and slowly and uniformly drop it into the four-necked flask, and the dropping is completed in about 2h; keep warm for 20min, then heat it to 95℃, and continue the reaction until there is no obvious hydrogen chloride discharged from the tail gas. Finally, the obtained product was filtered and then washed with 1,4-dioxane and anhydrous ethanol respectively, and then dried in a vacuum drying oven at a drying temperature of 90°C until the weight of the product did not change. In the above synthesis steps, the yield of PEPA was about 85.2%. A large amount of hydrogen chloride will be produced during the whole reaction process. Therefore, a hydrochloric acid absorption device is required to absorb the tail gas to prevent it from being discharged into the air to corrode the instrument and pollute the environment. The above reaction equation is shown below.

[0035]

[0036] Next, BPEPA is synthesized. The full name of BPEPA is: di-1-oxyphospha-4-hydroxymethyl-2,6,7-trioxabicyclooctane-1-phenyl-4-oxyphosphorus, and its appearance is a white solid powder. Since both phosphorus oxychloride and pentaerythritol are multifunctional substances, side reactions are prone to occur during the reaction. Therefore, in order to ensure the smooth progress of the BPEPA synthesis reaction, PEPA needs to be recrystallized with anhydrous ethanol to remove as many by-products as possible, thereby obtaining PEPA with higher purity. That is, in one embodiment of BPEPA, the specific steps are: under nitrogen protection conditions, 100ml of acetonitrile is added to a 250ml four-necked flask, which needs to be dehydrated with an activated 4A molecular sieve before use, and then used as a reaction solvent. Then, 39.6g, i.e. 0.22mol, of PEPA recrystallized from ethanol was added, and the temperature was raised to 75°C; after PEPA was completely dissolved under magnetic stirring, 23.23g, i.e. 0.23mol, of triethylamine was added as an acid binding agent, which needed to be dehydrated with an activated 4A molecular sieve before use. After the system was stabilized for 10 minutes, 19.5g, i.e. 0.1mol, of phenylphosphoryl dichloride was added to a 100ml constant pressure dropping funnel, and then it was slowly and uniformly added dropwise, and the addition was completed in about 1h. After keeping warm for 20min, the temperature was raised to 90°C and refluxed for 8h. After the reaction was completed, the product was filtered, and then the product was washed with acetonitrile and deionized water respectively. Finally, the product was dried in a vacuum drying oven at a drying temperature of 90°C until the weight did not change. In this embodiment, the yield of BPEPA was 60.4%. The reaction equation is shown below.

[0037]

[0038] Next, synthesize flame-retardant PA66. Specifically, the addition amount of fixed flame retardant BPEPA is 20wt%, and the addition amount of nano-SiO2 is 4%. Because there are amide bonds in PA66, the hygroscopicity of the raw material of PA66 is strong. Before use, PA66 should be dried at 100°C for 10 hours, and then blended, extruded and granulated with BPEPA. The specific extrusion process parameters are: the temperatures of each zone are 190°C, 210°C, 260°C, 280°C, 290°C, 290°C, 290°C, 290°C, 280°C, respectively; in addition, the temperature of the die is 280°C.

[0039] Specifically, pentaerythritol reacts with phosphorus oxychloride to generate PEPA. This reaction belongs to nucleophilic substitution. The specific reaction substitution process is as follows: the phosphorus atom in phosphorus oxychloride has a small electronegativity and is electropositive, while the -OH in pentaerythritol is a nucleophilic reagent, so -OH will attack the phosphorus atom. At this time, the chlorine atom is replaced by -OH, and the hydrogen atom on C1- and -OH combines to generate HC1. Similarly, the -OH on pentaerythritol and the remaining C1- of phosphorus oxychloride continue to undergo nucleophilic substitution until all the C1- in phosphorus oxychloride are combined with -OH, thus forming a stable bicyclic cage-like phosphate rigid structure. Since both pentaerythritol and phosphorus oxychloride contain multiple functional groups, by-products are easily generated if the reaction conditions are not well controlled. For example, when there is an excess of phosphorus oxychloride in the reaction system, the excess phosphorus oxychloride will further react with the remaining hydroxyl groups in the generated PEPA to generate by-products. If the phosphorus oxychloride droplet is accelerated too fast, another by-product will be generated. In order to reduce the probability of side reactions and obtain as much main product as possible, phosphorus oxychloride should be slightly excessive during the process. At the same time, phosphorus oxychloride should be added slowly and evenly, so that the obtained product can be basically the target product PEPA.

[0040] Furthermore, the chemical properties of the P-C1 bond in phosphorus oxychloride are very active and easily react with chemical substances containing active hydrogen. Therefore, in the preparation method of phosphorus silicon synergistic flame retardant nylon of the present invention, a non-protonic solvent should be selected. As a non-protonic solvent, 1,4-dioxane has a very low solubility of PEPA in it, which is conducive to the separation and washing of the product after the reaction. At the same time, phosphorus oxychloride is extremely sensitive to water, and even a trace amount of water in the solution will react with it, thereby causing the material balance ratio of phosphorus oxychloride and pentaerythritol to be destroyed, which is easy to induce side reactions in the process. Therefore, 1,4-dioxane should be added with activated 4A molecular sieves before use to remove water, thereby improving the purity of PEPA.

[0041] Furthermore, pentaerythritol is basically insoluble in 1,4-dioxane at room temperature. However, as the temperature increases, its solubility also increases. When the temperature rises to 85°C, more than half of pentaerythritol can be dissolved in the solvent. At this time, phosphorus oxychloride is added dropwise, and the two raw materials can be in relatively uniform contact in this solvent, which is conducive to the occurrence of the reaction. Since a large amount of heat is released during the entire reaction process, the temperature of the system rises sharply, and while taking away hydrogen chloride, part of the phosphorus oxychloride will also be taken away. At the same time, the product will also turn yellow and sticky, and the yield will be reduced. Therefore, the temperature should not be set too high after the addition of phosphorus oxychloride. Combined with the yield and energy consumption factors, it can be determined that the dropwise addition temperature of phosphorus oxychloride is set to 85°C for the most appropriate setting, and the temperature is raised to 95°C after the addition is completed until there is no obvious discharge of hydrogen chloride in the reaction.

[0042] Furthermore, the theoretical material ratio of pentaerythritol and phosphorus oxychloride is 1:1. In the actual preparation process, it is found that the yield of the product obtained by using the theoretical material ratio is very low. The reason is that this reaction is an exothermic reaction, which makes the system temperature easy to rise. The boiling point of phosphorus oxychloride is 105.8°C. If the temperature of the system rises to near the boiling point of phosphorus oxychloride, or even to above its boiling point; then phosphorus oxychloride will be taken away along with the discharge of hydrogen chloride. As a result, the mass of phosphorus oxychloride is reduced, which in turn destroys the material balance of the system, and the yield of the obtained product is not high. If too much phosphorus oxychloride is added, the yield will not be reduced. However, in practice, it is found that in the DSC test, multiple melting endothermic peaks are found in the spectrum, which indicates that more by-products are generated, resulting in a decrease in the purity of the product. Combining the two factors of yield and purity, the optimal molar ratio of phosphorus oxychloride and pentaerythritol in the synthesis process should be 1.1:1.0.

[0043] Specifically, the reaction of PEPA and phenylphosphoryl dichloride still belongs to a nucleophilic substitution reaction, but it is different from the synthesis conditions of PEPA, because an acid binding agent must be added during the second step of the reaction to generate the final product BPEPA. At this time, the acid binding agent not only improves the alkaline environment for the reaction, but also has a catalytic effect. More specifically, triethylamine is used as an acid binding agent in a preparation method of phosphorus silicon synergistic flame retardant nylon of the present invention. Triethylamine first reacts with phenylphosphoryl dichloride to generate an ammonium salt of triethylamine; then, triethylamine captures the hydrogen atom in the hydroxyl group on PEPA, and the hydroxyl group loses hydrogen to become an alkoxy anion; its nucleophilic ability is further increased, so that it can smoothly combine with the ammonium salt generated in the first step to finally generate the final product BPEPA.

[0044] Furthermore, an acid-binding agent is a chemical substance with alkalinity, and there are many types of it, which are usually divided into organic bases and inorganic bases. In the preparation method of a phosphorus-silicon synergistic flame-retardant nylon of the present invention, triethylamine, pyridine or anhydrous potassium carbonate can be selected as an acid-binding agent. Further comparison of the effect of the presence or absence of an acid-binding agent and the type on the yield of the flame retardant final product BPEPA shows that if no acid-binding agent is added, the reaction finally obtains a light yellow viscous substance, and no target product BPEPA is generated. If the type of acid-binding agent is changed, it is found that the yield of BPEPA is the highest when triethylamine is used as an acid-binding agent. It is further revealed as follows: When triethylamine is used as an acid-binding agent, the yield of BPEPA is the highest, reaching 60.3%; while the yields of BPEPA when pyridine and anhydrous potassium carbonate are used as acid-binding agents are 43.9% and 36.7%, respectively. The reason is that triethylamine and pyridine are both organic bases, but the alkalinity of triethylamine is greater than that of pyridine. The stronger the alkalinity, the more thorough the reaction, and the higher the yield of BPEPA. Anhydrous potassium carbonate is an inorganic base. When it is used as an acid-binding agent, potassium carbonate must first be decomposed to form potassium hydroxide, and then potassium hydroxide reacts with HCl to neutralize. This process is not conducive to the smooth occurrence of the reaction, so the product yield is the lowest.

[0045] More specifically, triethylamine is volatile and easily oxidized in the air. Therefore, before using triethylamine, the device should be purged with nitrogen, and then added to the flask after exhausting the air. And the whole reaction process should be carried out under the atmosphere of nitrogen. In addition, the reaction of PEPA and phenylphosphoryl dichloride will release heat, thereby taking away a small part of triethylamine. Therefore, the amount of triethylamine cannot be calculated according to the theoretical value, and triethylamine should be slightly excessive. At the same time, the dropping speed of phenylphosphoryl dichloride should be controlled so that the heat released by the reaction system instantaneously is not too high, so as to reduce the volatilization of triethylamine as much as possible, so that the yield and purity of the final product BPEPA can be made higher.

[0046] Furthermore, different molar ratios of PEPA to phenylphosphoryl dichloride, i.e., BPOD, also have an effect on the yield of the product BPEPA. From a series of experiments, it can be seen that as the ratio of n(PEPA):n(BPOD) increases, the yield of BPEPA also increases accordingly. This is because as the mass of PEPA in the system increases, the concentration of hydroxyl groups also increases, which can accelerate the speed of the nucleophilic substitution reaction, that is, promote the reaction to proceed more thoroughly in the positive direction. Among them, when the ratio of raw materials is 2.2:1, the yield increases from 56.3% to 58.4%; and when the ratio of raw materials continues to increase, the trend of increasing yield becomes smaller. Therefore, it can be determined that the optimal molar ratio of PEPA and BPOD is 2.2:1.

[0047] Furthermore, the molar ratio of PEPA to BPOD was fixed at 2.2:1, and a series of experiments were conducted with the reaction time as the independent variable. It can be seen that as the reaction time increases, the yield of BPEPA also increases. This is because the substitution reaction of PEPA and BPOD is carried out more thoroughly as time goes by. When the reaction time is 9h, the yield reaches a maximum of 59.8%, and when the reaction time is 8h, the yield can also reach 59.6%. Considering energy efficiency and environmental protection factors, the optimal reaction time is determined to be 8h.

[0048] Furthermore, the molar ratio of PEPA and BPOD was fixed at 2.2:1; the reaction time was fixed at 8h; and a series of experiments were conducted with the reaction temperature as the independent variable. It can be seen that the yield of BPEPA increases with the increase of the reaction temperature. Because the higher the temperature, the greater the activity of the molecules involved in the reaction, the more conducive to the reaction, thereby increasing the yield of BPEPA. Although the maximum value of 60.7% was reached at the reaction temperature of 100°C, the optimal reaction temperature was determined to be 90°C for economic and energy-saving factors. At this time, the yield can reach 60.4%.

[0049] Furthermore, the level of phosphorus content determines the flame retardant efficiency of the flame retardant. The phosphorus-containing flame retardant is heated in the condensed phase and decomposes in advance to generate acidic substances such as phosphoric acid and polyphosphoric acid, which can catalyze the formation of a carbon layer in the material. The carbon layer has the function of heat insulation and oxygen isolation, thereby achieving the purpose of flame retardancy. Specifically, the phosphorus content of the product can be determined by the quinoline molybdate method. The specific test steps are as follows: first, prepare a quinoline molybdate solution: weigh 70g of sodium molybdate and dissolve it in 150ml of deionized water, and this solution is marked as solution a. Then, after 85ml of concentrated nitric acid and 150ml of deionized water are mixed evenly, 60g of citric acid is weighed and dissolved in the solution, and this solution is marked as solution b. Then, solution a is slowly added to solution b, and solution c is obtained after stirring evenly. Accurately measure 5ml of quinoline and add it to a mixed solution of 35ml of concentrated nitric acid and 100ml of deionized water, and this solution is marked as solution d. Then, solution c and solution d are mixed and kept away from light for 24 hours, and then filtered and the filtrate is collected, and 280ml of acetone is added to the filtrate. Finally, deionized water is added to make the volume to 1000ml, and the quinoline molybdate solution is obtained after mixing evenly. Then, the phosphorus content is determined again, specifically: first accurately weigh Wg of the sample to be tested and add it to the test tube; then, 5ml of concentrated nitric acid and 5ml of concentrated sulfuric acid are measured and added thereto. The solution is boiled until it is colorless and transparent, and then transferred to a 250ml volumetric flask after cooling to room temperature, and the test tube is rinsed with distilled water 3-4 times, and finally fixed to volume. Measure 50ml of the solution and add it to a 250ml beaker, then add 50ml of deionized water, add 50ml of quinoline molybdate solution when the solution is heated to boiling, reheat to boiling and cool to room temperature, and then filter and collect the precipitate. The precipitate is dried at 120°C and weighed, recorded as A. The specific calculation method of phosphorus content is as follows: p=(A*0.07) / W*100%. According to the above formula, the phosphorus content of the final product BPEPA is calculated to be 19.03%, while the theoretical phosphorus content is 19.29%, which is close to each other.

[0050] Furthermore, PA66 should be dried at 100°C for 10h before use, and then blended, extruded and granulated with BPEPA; finally, it is injected into standard specimens by an injection molding machine to test its mechanical properties and flame retardant properties. Among them, the addition amount of BPEPA is 0%, 5wt%, 10wt%, 15wt% and 20wt% respectively. The process parameters of each zone of the extruder are: 190℃, 210℃, 260℃, 280℃, 290℃, 290℃, 290℃, 290℃, 280℃; the temperature of the head is 280℃. The process parameters of injection molding are: 190℃, 260℃, 270℃, 280℃, 275℃; the temperature of the nozzle is 275℃.

[0051] Specifically, the tensile strength test standard of the sample is in accordance with GB / T 1040-2006, the test specimen specification is 80mm*10mm*4mm, and the tensile rate is 20mm / min. The bending strength test of the sample is in accordance with GB / T 9341-2008, the test specimen specification is 80mm*10mm*4mm, and the tensile rate is 20mm / min. The notched impact strength test of the sample is in accordance with GB / T 1843-2008, the test specimen specification is 80mm*10mm*4mm, and the pendulum falls at an angle of 150°. The limiting oxygen index, or LOI, refers to the oxygen volume fraction concentration required for a polymer to just burn in an oxygen-nitrogen mixture, and is an index used to characterize the combustion behavior of a material. Materials with an LOI less than 22 are usually considered flammable materials, materials with an LOI between 22-27 are considered combustible materials, and materials with an LOI greater than 27 are considered flame-retardant materials. The test specimen is 80mm*1Omm*4mm in size. During the experiment, the specimen is fixed vertically in the glass combustion tube of the oxygen index meter. The base of the tube is connected to the nitrogen-oxygen mixed gas flow introduction device. The top of the specimen is ignited, and the oxygen fraction required to ignite the specimen is recorded, which is the limit oxygen index of the test specimen. The combustion performance of the specimen can be determined by the vertical method. Each group of experimental test specimens has five specimens, and the specifications of the specimens are 130mm*13mm*3mm. During the experiment, the upper end of the specimen is clamped vertically by 6mm with a fixture, and a medical absorbent cotton layer is placed 300mm away from the lower end of the specimen, with a specification of 80mmX50mm; the Bunsen burner is ignited at a distance of about 15Omm from the specimen, and the height of the flame is adjusted by adjusting the gas flow rate, which is about 20mm±2mm. The criteria for V-0 level are: the sample goes out within 10 seconds after ignition and there is no molten dripping or the dripping does not ignite the cotton wool; the criteria for V-1 level are: the sample goes out within 10-30 seconds after ignition and there is no molten dripping or the dripping does not ignite the cotton wool; the criteria for V-2 level are: the sample does not extinguish itself after ignition or the molten dripping does not ignite the cotton wool.

[0052] Furthermore, for the flame retardancy of PA66, it is difficult to achieve a good flame retardant effect by adding a single flame retardant. Usually, phosphorus flame retardants and nitrogen or silicon flame retardants are compounded to form phosphorus-nitrogen or phosphorus-silicon flame retardants, so as to exert their synergistic effect and achieve the ideal flame retardant effect. Therefore, nano-SiO2 can be added as a synergistic flame retardant. Among them, the addition amount of nano-SiO2 is: 0%, 1wt%, 2wt%, 3wt% or 4wt%. Specifically, with the increase of the addition amount of nano-SiO2, the tensile strength and flexural strength of flame-retardant PA66 show a trend of increasing first and then decreasing. When the addition amount of nano-SiO2 is 3wt%, the tensile strength and flexural strength of the system reach the maximum value, which are 66.55MPa and 80.73MPa respectively; when the addition amount of nano-SiO2 exceeds 3wt%, both strengths begin to decline, which is 13.3% and 12.6% lower than that of pure PA66. The reason for this changing trend is that nano-SiO2 has the effect of strengthening and toughening. Within a certain range of addition, it can improve the tensile strength and flexural strength of the system. However, when its addition exceeds a certain value, the dispersion of nanoparticles in the system becomes poor, causing the strength to decrease again.

[0053] Furthermore, the addition of nano-SiO2 did not change the impact strength of the system much. In general, nano-SiO2 caused the impact strength of the system to show a downward trend. When the addition amount of nano-SiO2 was 4wt%, the impact strength was 5.92kJ / m2, which was 18.2% lower than that of pure PA66. The main reason is that the nano-SiO2 particles are not evenly dispersed in the system. When the material is subjected to external force, the agglomeration effect of the nano-particles causes the system to be unable to absorb the impact energy in time.

[0054] Further, the flame retardant properties of BPEPA-nano-SiO2 flame retardant PA66 were tested by limiting oxygen index instrument and vertical combustion method, and the results are shown in Table 1; in Table 1, the comparative example is a common flame retardant PA66 product on the market; and in Examples 1 to 4, except for the content of BPEPA and nano-SiO2 as independent variables, the other components are the same. As can be seen from Table 1, with the increase of nano-SiO2 content, the limiting oxygen index of the flame retardant PA66 system gradually increases. When the addition amount of nano-SiO2 is 4wt%, LOI increases from 27.1% to 28.6%. Moreover, the vertical combustion performance of PA66 after adding nano-SiO2 can reach V-0 level. It can be seen that compared with the comparative example, after adding flame retardant BPEPA and nano-SiO2, the flame retardant properties of PA66 are significantly improved, indicating that the two flame retardants play a synergistic role, thereby achieving the purpose of flame retardancy.

[0055] Table 1: Flame retardant properties of BPEPA-nano-SiO2 flame retardant PA66

[0056]

[0057] In summary, the preparation method of phosphorus silicon synergistic flame retardant nylon of the present invention first uses pentaerythritol and phosphorus oxychloride as reaction raw materials to synthesize an intermediate PEPA with a bicyclic cage structure; then, PEPA is further reacted with phenylphosphoryl dichloride to prepare a new type of phosphorus flame retardant BPEPA with a highly symmetrical structure; at the same time, the phosphorus content of BPEPA is determined to be 19.03% by the quinoline molybdenum acetone method, which is close to the theoretical value. Then, the optimal synthesis process conditions of the flame retardant BPEPA are determined by the single factor experimental method: acetonitrile is used as the solvent, triethylamine is used as the acid binding agent, the optimal raw material molar ratio PEPA:BPOD=2.2:1, the optimal reaction time is 8h, and the optimal reaction temperature is 90°C. At this time, the yield of BPEPA can reach 60.4%. The flame retardant performance test shows that the flame retardant BPEPA and nano-SiO2 can improve the combustion performance of PA66. When the BPEPA addition amount is 20wt% and the nano-SiO2 addition amount is 4wt%, the LOI of the product is increased from 24% of pure PA66 to 28.6%, and the UL-94 vertical combustion performance of the product reaches the V-0 level. The flame retardant mechanism of phosphorus silicon type flame retardant is that during the combustion process, the phosphorus-containing flame retardant is thermally decomposed into phosphorus-containing depolymers at high temperatures. Such substances can catalyze the formation of the carbon layer of the material, and the decomposition products of the silicon-containing flame retardant during combustion can migrate to the surface of the carbon layer, making the formed carbon layer more stable. The synergistic effect generated by the phosphorus silicon synergy can obtain an ideal flame retardant effect; and it avoids the defects of the halogen-containing flame retardant in the prior art that a large amount of thick smoke and toxic and corrosive gases are generated during the combustion process, which damages instruments and equipment, and endangers personal safety and pollutes the environment. Therefore, the preparation method of a phosphorus silicon synergistic flame retardant nylon of the present invention solves the technical problem of poor safety of composite nylon materials in the prior art.

[0058] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0059] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing phosphorus-silicon synergistic flame-retardant nylon, characterized in that: It includes the following steps: S1: First, 1,4-dioxane and acetonitrile were dehydrated with activated 4A molecular sieves; then, 80 parts by volume of 1,4-dioxane were added to a 250-part four-necked vessel under nitrogen protection and mechanical stirring; S2: Add 27.2 parts of pentaerythritol and raise the temperature to 85°C; after the pentaerythritol is partially dissolved, add 33.66 parts of phosphorus oxychloride into 100 parts by volume of the constant pressure dropping funnel, and slowly and uniformly drip it into the four-mouth container, and the dripping is completed in 2 hours; After keeping the temperature for 20 minutes, raise the temperature to 95°C and continue the reaction until no obvious hydrogen chloride is emitted from the tail gas; S3: Then, in a vacuum drying oven, the mixture is treated at a drying temperature of 90° C. until the weight of the product does not change, to obtain the intermediate product PEPA; S4: Next, under nitrogen protection, 100 parts by volume of acetonitrile was added to another four-necked vessel containing 250 parts by volume; then, 39.6 parts of PEPA recrystallized from ethanol was added, and the temperature was raised to 75° C.; S5: After PEPA is completely dissolved under magnetic stirring, add 23.23 parts of triethylamine as an acid binding agent. S6: After the system is stable for 10 minutes, add 19.5 parts of phenylphosphoryl dichloride into a 100 volume parts constant pressure dropping funnel, and then slowly and uniformly add it dropwise for 1 hour. After keeping the temperature for 20 minutes, raise the temperature to 90°C and reflux for 8 hours; S7: After the reaction is completed, the product is filtered, and then the product is washed with acetonitrile and deionized water respectively; and then the product is dried in a vacuum drying oven at a drying temperature of 90° C. until the weight does not change; thereby BPEPA is synthesized; S8: pre-dry PA66 at 100°C for 10 hours; then, blend and extrude PA66, BPEPA and nano-SiO2 together; Then, it is granulated; the process parameters of each zone of the extruder are: 190℃, 210℃, 260℃, 280℃, 290℃, 290℃, 290℃, 290℃, 280℃; the temperature of the head is 280℃; the addition amount of BPEPA is 5wt%, 10wt%, 15wt% or 20wt%; the addition amount of nano-SiO2 is 1wt%, 2wt%, 3wt% or 4wt%.

2. The method for preparing a phosphorus-silicon synergistic flame-retardant nylon according to claim 1, characterized in that: In step S5, pyridine or anhydrous potassium carbonate is used instead of triethylamine as the acid binding agent.

3. The method for preparing a phosphorus-silicon synergistic flame-retardant nylon according to claim 1, characterized in that: When the addition amount of BPEPA is 20wt%, the addition amount of nano-SiO2 is 4wt%.

Citation Information

Patent Citations

  • Rare earth flame retardant composite nylon material

    CN102382297A

  • Fluorophenyl and phosphate structure-containing novel phosphorus-silicon flame retardant and preparation method and application thereof

    CN104725668A

  • Low-filling efficient synergistic flame-retardant nylon 66 and preparation method thereof

    CN114133734A